Застосування хмарних технологій в галузі мікро- та нанотехнологій - Бородін, Я. В.; Стрілкова, Т. О. (ХНУРЕ, 2025)
The report explores the application of cloud technologies in research processes within micro- and nanotechnologies, specifically for modeling the interaction of optical radiation with semiconductor photostructures. Key scenarios for utilizing cloud computing are analyzed, including process simulation, data analysis of research results. Special attention is given to the use of Google Colab for processing and visualizing experimental data, as well as the creation of mental maps using the Coggle.it service to systematize the stages of the experiment. The modeling of the stochastic process of photon absorption by semiconductor structures is performed the parameters of radiation and the internal noise of the photodetector. The obtained results are presented in the form of diagrams generated using the Matplotlib library, providing a clear interpretation of the data.
Keywords: мікротехнології; нанотехнології